'I'm never going to be part of it': identity, investment and learning Korean. Issue 2 (7th February 2018) - Gearing, Nigel; Roger, Peter
ABSTRACT: This study investigated the willingness of 14 English-speaking EFL instructors living and working in South Korea to invest in practices connected with learning and using the Korean language. A model of investment for the 'new world order' (Darvin, R., and B. Norton. 2015. "Identity and a Model of Investment in Applied Linguistics." Annual Review of Applied Linguistics 35: 36–56. doi:10.1017/S0267190514000191) was used as a theoretical lens through which to analyse the interview data to explore how attempts to negotiate membership into local communities of practice affected participants' investment in Korean, as well as the ways in which participants interpreted and reacted to perceived inequities of power between themselves and these communities of practice. This study found that the ways in which participants perceived that they were positioned as native English speakers tended to work against sustained investment in Korean language learning, as potential returns in terms of valued forms of capital seemed very limited. For the vast majority of participants, entry into local communities of practice did not occur, but where a sense of belonging was evident, investment in the language was seen as a key to enabling deeper levels of engagement.